This Isn’t Just a Phantom, Menopause, But You Can Vent Your Feelings - Qualitative Evaluation of Evidence Based Health Information (EBHI) Material - B, Berger; K, Boehm (Journal of Women's Reproductive Health, 2017)
Objective Because of the increased demand for the availability of independent information regarding the efficacy, the lack of efficacy and the possible harm of medical interventions, the study aims to evaluate the information package „Menopause", published by the German Institute for Quality in Healthcare (IQWiG). Methods: Qualitative, guideline-based interviews, carried out in n=41 women (40-63 years). The analysis of transcripts was carried out according to Mayring. Results Information perception of women who could use the material could be summarized into the following: (1) Information were perceived as independent and deemed trustworthy. (2) Scientific study results were unknown but welcomed. (3) Decision aids are useful but need further communicative support. (4) Women requested suggestions for empowerment and self-help. (5) Some women are better accessible through experiences. (6) Women who did not take on any information presented in the material. Conclusions: Through evidence-based health information (EBHI) and decision aids interviewed women can be enabled to make informed decisions concerning their health care. Health information should include the relevant context factors. However, not all women could be reached. Practice implications Not only the implementation of independent EBHI into the structure of healthcare but also communicative services including biographical aspects and self-help strategies are needed.
Keywords: Menopause; Evidence-Based Health Information; Health Literacy; Patient Empowerment; Decision Aids; Qualitative Research